A CERÂMICA NO ENSINO DE ARTES VISUAIS: Um estudo no Centro de Ensino Paulo VI em São Luís (MA)). - MARQUES, Walter Rodrigues (2019)
The dissertation approaches the Ceramics as content of the curricular component Art in the teaching of Visual Arts in High School aiming to form identity subjects with notions of belonging. The reflection on my Eurocentric practice as an art teacher has troubled me too much. LDB 9.394 / 96 advises that part of the curriculum be diversified and regionalized. I realized this was not present in my classroom work. And it was then that I awoke to the search for teaching materials that could subsidize my art classes with the regional / local content of the artistic and cultural manifestations and no substantial material regarding regionality was found. The textbooks of the PNLD (National Textbook Program) 2018-2020 of Art were analyzed and only one reference to the Maranhão culture was found in one of the books - bumba meu boi. From this, among so many cultural manifestations of Maranhão, in order to make meaningful classroom practice, strengthen identity ties as well as relations with the earth, was chosen the pottery as a language to be worked in the Art discipline, because the PNLD books only use it as an informative illustration of cultures (Greek culture, Tupiguarani culture) through vases and funeral urns. Therefore, a didactic-pedagogical proposal was prepared in book form with a summarized content of ceramics (Africa, Asia, Europe, America) directing to Brazil and tapering to Maranhão. Pottery was treated in this study as historical-cultural rather than artistic, however, the students' practice focused on artistic practices, as they participated in the whole process of creating ceramic pieces. The aim of the didactic proposal was to provide knowledge about this aspect of Art as well as to provide the recognition of Ceramics as a productive activity of local culture, its importance and applicability in tiles, civil construction, with special emphasis on artisanal and cultural ceramics. consequently artistic, such as crafts and utilitarian ceramics. Therefore, allowing the recognition of students' self through Ceramics as subjects of identity belonging. The proposal is based on the guidelines of the Law of Guidelines and Bases of National Education (LDB 9.394 / 96) in art. 26, § 2 on the teaching of art, especially in its regional expressions. This is a mixed research whose data collection took place from May to June 2019 at the Paulo VI Teaching Center in São Luís (state school) and had as research subjects the students of a third grade class. with which a didactic-pedagogical proposal was applied in Visual Arts having as content the Ceramics. With the accomplishment of the research, that is configured in the first moment as didactic material with the ceramic as content, in a second moment with the application of the didactic material in the classroom in the basic education, it was intended to construct a proposal that contemplates didactic sequences portraying the socioeconomic and artistic aspects of Maranhão in order to subsidize the pedagogical actions aimed at the formation of the subject belonging by the reflection on the identity at the local level, without losing the global dimension - the being-in-the-world. The study is theoretically anchored in Silva (2015), Geertz (2014), Bhabha (2013) and Hall (2006), who discuss identity and cultural belonging in postmodernity as a matter of agency from the perspective of postcolonial studies. ; Prous (2011), Tirapeli (2006), Panachuk, (2016), Leite Filho (2016), Flag (2016), Navarro (2016), the encyclopedias of museums, Museu Paraense Emílio Goeldi (1999) and the exhibition catalogs of the IDESP-PARÁ (1973), which reveal the North and Northeast of Brazil relating them to indigenous cultures and their ceramic productions with recent forays into archaeological studies in this region; Barbosa (2010; 2012), Selbach (2010), Schlichta (2009), Ferraz and Fusari (2009), Dewey (2010), Ostrower (2004), Derdyk (2010), who discuss and problematize the teaching and creative process in art. as well as the place of art in school; Saviani (2008), Arroyo (2013), Goodson (2013), Gauthier (2013), Sacristan (2000), Zabalza (2004), Pacheco (2003; 2005), Lopes and Macedo (2011), Freire (1980), Apple (2006) and Young (2011), who discuss education, curriculum and teacher education, linking the discussion to the recurring transformations of educational policies; the Constitution of the Federative Republic of Brazil of 1988 (2008), the LDB 9.394 / 96 and its amendments, the National Curriculum Parameters (2002); the national and state curriculum guidelines and guidelines, and other documentary sources that have been threaded into this fabric. We hope that this study can contribute to the realization of significant Art Education in schools and its contribution to a socially fair, democratic and artistically balanced school.